(untitled) (KYAMC Journal, 2020)
Mediastinal tumors are slow growing tumors of rare entity. They usually affect middle aged people ranging from 30-50 years. When they grow, may compress surrounding structures and produce symptoms such as cough, chest pain, chest tightness and respiratory distress. The most common anterior mediastinal masses are thymoma and lymphoma. Posterior mediastinal tumors are mainly neuroendocrine tumors. Diagnosis depends upon proper clinical history, X-ray chest, CT scan and if necessary CT guided FNAC. Sometimes hormonal tests such as -hCG and AFP may be needed for Germ cell tumors. Treatment is usually by wide surgical excision and biopsy followed by chemo or radiotherapy. Hodgkin’s and Non-Hodgkin’s Lymphoma are usually treated by chemotherapy. For proper management, widespread suspicion and diagnostic facilities should be available before the start of treatment. KYAMC Journal Vol. 11, No.-3, October 2020, Page 161-163